New low bandgap near-IR conjugated D–A copolymers for BHJ polymer solar cell applications. Issue 12 (2nd March 2016) - Keshtov, M. L.; Kuklin, S. A.; Radychev, N. A.; Nikolaev, A. Y.; Ostapov, I. E.; Krayushkin, M. M.; Konstantinov, I. O.; Koukaras, E. N.; Sharma, Abhishek; Sharma, G. D.
Abstract : Two ultra low bandgap ( E g ≤ 1.2 eV) D–A copolymers, with UV to near-IR absorption, are synthesized and used as donors for polymer solar cells, obtaining PCEs of 7.27% and 6.68%. Abstract : We synthesized two novel ultra low bandgap donor–acceptor (D–A) copolymers ( E g ≤ 1.2 eV), containing the thiadiazoloquinoxaline unit as the main electron accepting unit (A) and benzodithiophene (BDT) and dithienosilole (DTS) as different donor units (D), denoted asP1 andP2, respectively, using the cross-coupling Stille reaction. The copolymers possess light absorption ranging from UV (350 nm) to near-IR (1300 nm) with optical bandgaps of 1.16 eV and 1.08 eV, respectively. Quantum-chemical calculations and experimental data were compared for proposing a more detailed concept for the optical and electronic properties of these copolymers which can be used as donors for polymer solar cells (PSCs). The PSCs based on optimizedP1 :PC71 BM andP2 :PC71 BM showed overall power conversion efficiencies (PCEs) of 4.32% and 3.48%, respectively. AlthoughP2 possesses a broad absorption coverage of up to 1300 nm, the lower PCE may be attributed to the low J sc, due to the poor driving force for exciton dissociation, since the LUMO offset with PC71 BM is less than 0.3 eV. The PCE has been significantly increased to 7.27% and 6.68% for solvent vapor annealing (SVA) treatedP1 :PC71 BM andP2 :PC71 BM active layers, respectively. This improvement arises from the appropriate nanoscale morphology and an increase in hole mobility, induced by the SVA treatment of the active layers.